New Applications of JAK/STAT Inhibitors in Pediatrics: Current Use of Ruxolitinib - Annalisa Marcuzzi; Erika Rimondi; Elisabetta Melloni; Arianna Gonelli; Antonio Giacomo Grasso; Egidio Barbi; Natalia Maximova (Pharmaceuticals, 2022)
Janus kinases (JAK) are a family of tyrosine kinases (JAK1, JAK2, JAK3, and TYK2) that transduce cytokine-mediated signals through the JAK–STAT metabolic pathway. These kinases act by regulating the transcription of specific genes capable of inducing biological responses in several immune cell subsets. Inhibition of Janus kinases interferes with the JAK–STAT signaling pathway. Besides being used in the treatment of cancer and inflammatory diseases, in recent years, they have also been used to treat inflammatory conditions, such as graft-versus-host disease (GVHD) and cytokine release syndrome as complications of allogeneic hematopoietic stem cell transplantation and cell therapy. Recently, the FDA approved the use of ruxolitinib, a JAK1/2 inhibitor, in the treatment of acute steroid-refractory GVHD (SR-aGVHD), highlighting the role of JAK inhibition in this immune deregulation. Ruxolitinib was initially used to treat myelofibrosis and true polycythemia in a high-dose treatment and caused hematological toxicity. Since a lower dosage often could not be effective, the use of ruxolitinib was suspended. Subsequently, ruxolitinib was evaluated in adult patients with SR-aGVHD and was found to achieve a rapid and effective response. In addition, its early low-dose use in pediatric patients affected by GVHD has proved effective, safe, and reasonably preventive. The review aims to describe the potential properties of ruxolitinib to identify new therapeutic strategies.